What draws you here? intention of youth’s participation in adventure tourism activities / Nor Farhana Usamah and Faiz Izwan Anuar - Usamah, Nor Farhana; Anuar, Faiz Izwan (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Adventure tourism is one of the niche tourism concepts that recently attracts a substantial number of travellers. This kind of tourism is more likely related to high level of activities from which individuals draw personal satisfaction from some unusual sight, activity or accomplishment. Young people or specifically called as youth are those who involve more in this kind of activities as they act as a catalyst for tourism industry development and nowadays they are more into adventure tourism activities which they contributed about 86% in experiencing a new destination when they travel. This study investigated the push and pull motivation factors that influenced their intention towards adventure tourism. The results found that push and pull factors were both significantly influenced the intention to participate in adventure tourism. However, push factors resulted in being the strongest influencer in motivating the youth to be engaged in this type of activities. Hence, implications of these results suggest that the key attributes need to be investigated to understand the motivations in participating adventure tourism activities specifically among youth.